2015
DOI: 10.1309/lm7ihv2nji1phmxc
|View full text |Cite
|
Sign up to set email alerts
|

Expression of FOXP1 and Colorectal Cancer Prognosis

Abstract: In our case series, loss of FOXP1 was associated with reduced survival rates in CRC tissue. Also, FOXP1 affects proliferation and inflammatory reaction in colorectal neoplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…In total, 2468 tumor patients from 9 different countries were included in our meta-analysis, and the studies were published from 2004 to 2015. The tumor types contained are as follows: DLBCL 13 14 15 20 24 25 26 27 28 29 , breast cancer 16 30 31 , endometrial cancer 17 , MALT lymphoma 14 32 33 34 , hepatocellular carcinoma 35 , NSCLC 18 , prostate cancer 12 , colorectal cancer 36 and epithelial ovarian cancer 37 . As for the survival outcomes, 22 eligible studies were divided into 31 datasets: 20 for OS, 4 for PFS, 3 for RFS, 2 for DFS, 1 for CSS and 1 for FFS ( Table 1 and Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 2468 tumor patients from 9 different countries were included in our meta-analysis, and the studies were published from 2004 to 2015. The tumor types contained are as follows: DLBCL 13 14 15 20 24 25 26 27 28 29 , breast cancer 16 30 31 , endometrial cancer 17 , MALT lymphoma 14 32 33 34 , hepatocellular carcinoma 35 , NSCLC 18 , prostate cancer 12 , colorectal cancer 36 and epithelial ovarian cancer 37 . As for the survival outcomes, 22 eligible studies were divided into 31 datasets: 20 for OS, 4 for PFS, 3 for RFS, 2 for DFS, 1 for CSS and 1 for FFS ( Table 1 and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Second, decreased expression of FOXP1 is an unfavorable factor for solid tumors. As the meta-analysis results were pooled from breast cancer 16 30 31 , endometrial cancer 17 , hepatocellular carcinoma 35 , NSCLC 18 , prostate cancer 12 , colorectal cancer 36 and epithelial ovarian cancer 37 , and combined with further evidence from neuroblastoma 11 , we considered that this finding may be applicable to all solid tumors. Third, FOXP1 protein may function as a tumor promoter in lymphomas and act as a tumor suppressor in solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…22 Of important note, CCR1 also was identified to be regulated by FOXP1 in colon cancer cell lines. 23 As such, we attempted to determine the role of CCR1 in FOXP1 siRNA-induced growth and invasion of lung cancer cells, we transfected A549 and PC9 cells with CCR1 siRNA in addition to FOXP1 siRNA transfection and measured the cancer cell growth and invasion. As shown in Figure 4, knockdown of CCR1 reduced the growth and invasion of lung cancer cells.…”
Section: Chemokine Signaling Pathway Is Involved In Foxp1mediated Tummentioning
confidence: 99%
“…FOXP1 has been located to chromosome 3p14.1, a chromosomal locus that has been shown to be disrupted in a series of solid tumors [ 25 ]. Many studies have revealed that FOXP1 is aberrantly expressed in several types of cancers and its expression frequently has a significant correlation with aggressive malignant phenotypes of tumors and poor prognosis in patients [ 11 , 12 , 16 , 17 , 18 , 19 , 21 , 26 , 27 ]. Therefore, these findings suggest that FOXP1 indeed plays an important role in solid cancers and led us to investigate the role of FOXP1 in HCC.…”
Section: Discussionmentioning
confidence: 99%